Recent Advances in Boron-Containing Materials - Aydin, Metin (IntechOpen, 2020)
The aim of this book is to represent an overview of applications of boron-based materials in the field of material science to biomedicine. This text is a collection of selected research articles and reviews, including recent efforts in several applications of boron-containing materials. All chapters are written by researchers who are active on the frontline. The chapters in this book will be helpful for many students and researchers involved in the field of boron-based material